Polymorphic ventricular tachycardia on a young patient - Yontar, Osman Can; Tenekecioglu, Erhan; Karaagac, Kemal; Tutuncu, Ahmet (Asian Journal of Medical Sciences, 2014)
Twelve-lead electrocardiogram is the most frequently utilized device for cardiologists. Although it is a basic device, great attention must be paid when it comes to give vital decisions. DOI: http://dx.doi.org/10.3126/ajms.v6i1.10804 Asian Journal of Medical Sciences Vol.6(1) 2015 127-128